Wielka Matka I. Kuran-Bogucka. - Kuran-Bogucka, Irena (1920-1995) (Kuran-Bogucka, Irena (1920-1995). Metopy barbarzyńskie, 1964)
Przedstawia siedzącą po turecku nagą kobietę trzymającą na rękach niemowlę.